A study of culture of Muslims in Myanmar: collection of cultural resources for national identity - U Tun Aung, Maulana Akbar Shah (Infobase Creation Sdn Bhd, 2016)
Since the contemporary world has seen many atrocity and inequitably with regards to the Muslims of Myanmar, it is liable to a peace maker to trace out the reality of their problems as to why the problem started, when they settled in Myanmar and what are the matters causing their instability and suffering. As a matter of facts, many scholars have already written about their problems and the solutions from different viewpoints and perspectives, but the cultural aspect of them has been rarely touched by any scholar. Since the role of culture signifies custom, dress, language, tradition, religion, food, music’s and ways of life of a group of people in certain places, it can support the authenticity and originality of Muslims of Myanmar. When culture of a nation is a contributing factor to determine eligibility of the national identity, a proper survey and study of cultural information of a race is essential. It is because, culture of a race or a community cannot be surfaced in a short period of time and it is a product of long term stay in a place. The land where they stay facilitates them to love its environment, people inspiring patriotism towards their land. That is the reason; this paper is going to highlight a particular area of the culture of Muslims of Myanmar. A qualitative research method is applied to search relevant data and information through available sources including books, magazines, journals, newspapers and library sources. Some of the analysis and interviews were also conducted individually and collectively.